PEMBELAJARAN MENYENANGKAN BERBASIS EXPERIENTIAL LEARNING DALAM MEWUJUDKAN OPTIMALISASI KOLABORASI SISWA SEKOLAH DASAR - Sava Dewnie Zada Ulima; Dwi Anggraeni Siwi (STKIP Subang, 2026)
Collaboration skills are one of the important competencies that need to be developed in elementary school learning. However, the learning process requires approaches that actively engage students and provide meaningful learning experiences. This study aimed to describe the implementation of joyful learning based on Experiential Learning and its impact on optimizing the collaboration skills of fifth-grade students at SD Negeri Mertan 03. This study employed a qualitative approach with a descriptive method. The research subjects consisted of the fifth-grade teacher and fifth-grade students of SD Negeri Mertan 03. Data were collected through observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The validity of the data was tested using source triangulation and technique triangulation. The results showed that joyful learning based on Experiential Learning was systematically implemented through four stages, namely concrete experience, reflection, concept formation, and application. The implementation of this learning approach demonstrated the optimization of students’ collaboration skills, which were reflected in students’ contributions within groups, responsibility in completing tasks, and the ability to work cooperatively with group members. Therefore, joyful learning based on Experiential Learning is able to create meaningful learning experiences while supporting the development of collaboration skills among elementary school students.